Healthcare utilisation for febrile diseases in northern Tanzania: a randomised population-based cluster survey - Blandina T Mmbaga; John A Crump; Julian T Hertz; Matthew P Rubach; Venance P Maro; Kajiru G Kilonzo; Deng B Madut; Rebecca Bodenham; Gwamaka William; Timothy A Peter (BMJ Global Health, 2025)
Background We conducted a randomised population-based cluster survey in northern Tanzania to assess care-seeking behaviours in the context of a febrile illness. Our objectives were to determine the most effective points for intervention during initial fever case management and to characterise factors associated with care-seeking.Methods The primary sampling unit, or cluster, was the village, and the secondary sampling unit was the household. Villages were selected in a population-weighted fashion, and households were randomly selected within each village. At each household, surveys were administered to determine hypothetical healthcare utilisation patterns for the following febrile syndromes: (1) fever, (2) fever >3 days, (3) fever with diarrhoea, (4) fever with difficulty breathing and (5) fever with confusion. Descriptive analyses were used to evaluate healthcare utilisation for each syndrome at the level of the individual household member, and multivariable logistic regression models were constructed to identify factors associated with care-seeking at a hospital for fever with difficulty breathing or confusion.Results From February through October 2018, we enrolled 718 households with a total of 2744 household members. Dispensaries were the leading site of care-seeking for fever (n=1167, 42.5%), fever >3 days (n=1318, 48.0%) and fever with diarrhoea (n=1218, 44.4%). In contrast, hospitals were the leading site for care-seeking for fever with difficulty breathing (n=1436, 52.3%) and fever with confusion (n=1521, 55.4%). Households in the highest wealth quartile had higher odds of reporting that household members would seek hospital care for fever with difficulty breathing or confusion.Conclusion In summary, our results suggest that lower-level health facilities, such as dispensaries, play an important role in the initial management of most febrile syndromes. Further research is needed to define the quality of fever case management within such facilities. Finally, our findings provide further evidence that socioeconomic status modifies health-seeking patterns.